El papel de las ideas y las políticas en el cambio estructural en México (1982–2005): un balance preliminar - Cordera Campos, Rolando (2006)
This paper deals with Mexico’s economic history from 1982 early crisis and 1994 late one. It analysis the transit of an import substitution model and state oriented economic policy to an open market economy in a close relationship to U.S. economy and free trade agreement. This transit meant also a change in politics, after many years of PRI’s dominance. It also aim to advice about the so-called «demographic bonus», provided a slowing down of the birth rate and its consequence on further employment needs.